2022
DOI: 10.3390/vaccines10091465
|View full text |Cite
|
Sign up to set email alerts
|

Oral Vaccination Using a Probiotic Vaccine Platform Combined with Prebiotics Impacts Immune Response and the Microbiome

Abstract: Unique to mucosal vaccination is the reciprocal influence of the microbiome and mucosal immune responses, where the immune system is constantly balancing between the clearance of pathogens and the tolerance of self-antigen, food, and the microbiota. Secretory IgA plays a major role in maintaining the homeostasis of a healthy gut microbiome. Natural polyreactive IgA often coats members of the commensal microbiota to aid in their colonization, while high-affinity specific IgA binds to pathogens resulting in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…IgA is the predominant antibody in the gut that binds to pathogens and commensals, preventing their translocation across the mucosal barrier. Using a probiotic-based mucosal vaccine with Lactobacillus acidophilus , Fox et al [ 159 ] showed that a potent, diverse IgA response could be elicited , which could help with colonization resistance. In another study, Slack and colleagues designed an oral vaccine using genetically modified Salmonella enterica capable of setting evolutionary traps for prophylaxis treatment in a mouse model[ 160 , 161 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…IgA is the predominant antibody in the gut that binds to pathogens and commensals, preventing their translocation across the mucosal barrier. Using a probiotic-based mucosal vaccine with Lactobacillus acidophilus , Fox et al [ 159 ] showed that a potent, diverse IgA response could be elicited , which could help with colonization resistance. In another study, Slack and colleagues designed an oral vaccine using genetically modified Salmonella enterica capable of setting evolutionary traps for prophylaxis treatment in a mouse model[ 160 , 161 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Following oral vaccination, a cascade of complicated cellular processes is set in motion, which mainly take place in the structured lymphatic tissues and the mucosal LP of the gastrointestinal tract. A number of important immune cells are involved in this particular process, including DCs, naïve T cells, and B lymphocytes [ 84 , 85 ].…”
Section: Stimulating Intestinal Immune Responses Through Oral Vaccina...mentioning
confidence: 99%
“…Efficient operation of these channels enables the assimilation of nutrients while preventing the entry of foreign substances [ 36 ]. To effectively stimulate an immune response, oral cancer vaccines should be specifically formulated to target enterocytes, especially M cells [ 2 , 85 ].…”
Section: Challenges In Oral Delivery: Gastrointestinal Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated the feasibility of using Lactobacillus acidophilus (LA) as a vaccine candidate by developing recombinant LA (rLA) strains for the mucosal pathogen HIV-1-expressing MPER and Gag epitopes along with IL-1β or the TLR5 ligand Salmonella enterica serovar Typhimurium flagellin (FliC) as adjuvants [ 28 , 31 , 32 ]. Oral immunization with these rLA-generated antigen-specific serum IgG, mucosal IgA, and B-cells in mucosal tissues (female reproductive tract and large intestine).…”
Section: Introductionmentioning
confidence: 99%